Analysis of the Effect of External Environment and Marketing Strategy on the Marketing Performance of MSME Fashion - Kadar Nurjaman (HK-Publishing, 2022)
AbstractThe purpose of this study was to determine the effect of the external environment and marketing strategy on the marketing performance of fashion SMEs in the Bandung area. This research use quantitative methods. Primary and secondary data were analyzed in this study. The study's preliminary results comes from questionnaires administered to ten respondents using the Likert scale. Validation tests, reliability tests, and hypothesis testing were used in this study's data analysis. According to the statistics and study findings, external environmental variables have a positive but non-significant effect on marketing performance; and marketing strategy has a positive but non-significant effect on marketing performance.Keywords: Analysis, Influence, External Environment, Marketing Strategy, Marketing Performance, MSMEs. AbstrakTujuan penelitian ini adalah untuk mengetahui pengaruh lingkungan eksternal dan strategi pemasaran terhadap kinerja pemasaran UKM fashion di wilayah Bandung. Penelitian ini menggunakan metode kuantitatif. Data primer dan sekunder dianalisis dalam penelitian ini. Hasil awal penelitian ini berasal dari kuesioner yang diberikan kepada sepuluh responden dengan menggunakan skala Likert. Uji validasi, uji reliabilitas, dan uji hipotesis digunakan dalam analisis data penelitian ini. Menurut statistik dan temuan studi, variabel lingkungan eksternal memiliki pengaruh positif tetapi tidak signifikan terhadap kinerja pemasaran; dan strategi pemasaran berpengaruh positif namun tidak signifikan terhadap kinerja pemasaran.Kata kunci: Analisis, Pengaruh, Lingkungan Eksternal, Strategi Pemasaran, Kinerja Pemasaran, UMKM.